Modelling of heat transfer In biological tissue by interval FEM - Jasiński, Marek; Pownuk, Andrzej (Computer Assisted Methods in Engineering and Science; Vol 7 No 4 (2000), 2023)
In this paper, an algorithm of calculation of extreme values of temperature based on interval arithmetic is presented. Many mechanical systems with uncertain parameters can be described by a parameter dependent system of linear equations K( )T = B( ). Using natural interval extension of a real function, one can transform the system of linear equations into the system of linear interval equations K()T = B(). Solution of the system of linear interval equations always contains the exact solution of the parameter dependent system of equations. A new method of computation of extreme values of mechanical quantities based on the monotonicity test is introduced. This method can give exact solution of a parameter dependent system of equations.